Identificação de barreiras a trombólise em pacientes na fase aguda do acidente vascular cerebral isquêmico - Fonseca, Luiz Henrique de Oliveira (2012)
Introduction: Stroke (cerebrovascular accident) is a major cause of functional sequelae and death in Rio de Janeiro and Brazil and thrombolysis is an important therapeutic strategy proven to reduce morbidity. This therapy is indicated for patients with up to 4.5 hours of symptom onset. The process of use of thrombolytic therapy in stroke can be evaluated as a sequential set of critical steps that can be measured and managed to optimize its use in eligible patients. Objectives: To assess the types of clinical and administrative barriers, to thrombolytic therapy in patients with acute stroke treated in the emergency room of a private hospital in Rio de Janeiro, Brazil. Methods: Retrospective cohort study of consecutive patients admitted to the emergence of a private hospital in the city of Rio de Janeiro (RJ) between January 2009 and October 2011. The charts of all patients with clinical suspicion of stroke were recorded file card, and analyzed the clinical characteristics (age, sex, risk factors, NIHSS, among others), the time spent in various stages of clinical protocol and the barriers and administrative use of thrombolysis in non-eligible patients were evaluated in the analysis of medical records. Results: Between 01/2009 to 10/2011 were admitted and treated 257 patients with clinical suspicion of stroke and 156 ischemic stroke. The male was more prevalent (53.3%) and mean age was 76.3 years (± 12.7). Of the total, 41 pts came within the "therapeutic window" of symptom onset and the NIHSS range for thrombolysis. Of these, 30 were confirmed by neuroimaging, however in 19 (63.3%) thrombolysis was detected a barrier. Barriers by 10 clinics, the relation of clinical barriers consist of: 1 (10%) with aortic dissection, 3 (30%) patients were excluded for clinical decision team (recent gastrointestinal bleeding, dementia, and elderly patients with limited life ), 1 (10%) with elevated BP and difficult to control, one (10%) with sequelae of recent stroke and 4 (40%) showed improvement in NIHSS. Administrative barriers 9 pts were present in the relationship of these being composed of: 1 (11.1%) leack of neurologist assessment 1 (11.1%) of the evaluation time exceeding neurologist 270min, 3 (33.3% ) with time of onset of symptoms coupled with the time of first image by extrapolating the therapeutic window, 2 (22.2%) with time of onset of symptoms coupled with assessment of the neurologist extrapolating the therapeutic window and in 2 (22.2%) patients, the attending physician did not allow the administration of thrombolytic therapy. In total 18 pts (11.5% of ischemic) were thrombolized, 11 with eligibility criteria and in 7 pts eligibility criteria have been violated at the time of thrombolysis. There were 13 (5.1%) deaths among the 257, and 3.8% between ischemic and one between 18 thrombolized. Still, the 20 patients with completed within the therapeutic window and without clinical contraindications, nine (45%) were prevented by administrative barriers. Conclusion: After defining diagnoses and which patients are eligible to "therapeutic window" compatible NIHSS and compatible imaging test definer of ischemic clinical barriers arise related comorbiditie and administrative barriers are related to the need optimization of the processes involved in care, as well as improving the information available to the lay population of patients and their families, besides the medical class, that of patient care. The barriers are part of the process and allow a critical evaluation of these with subsequent improvement actions. We point out that 2 in 3 patients within the therapeutic window and NIHSS in the range did not undergo thrombolysis because of barriers. The clinical and administrative barriers had an incidence equal, among those eligible. Among the administrative barriers stand out two factors related to the processes, time dependent, ( first image and the neurologist evaluation time) liable to management, while in the context of the barriers that the observed clinical improvement in NIHSS was most often this does not last susceptible to intervention.